Komodifikasi dan Fragmentasi Identitas Buruh Perempuan Pabrik Rokok dalam Novel Khutbah di Bawah Lembah Karya S. Jai : Perspektif Feminisme Marxis - Subiyakti, Evi Titin; Harjito, Harjito; Septiana, Ika (Jurnal Bahasa dan Sastra, 2026)
This article analyzes the representation of female cigarette workers in S. Jai’s Khutbah di Bawah Lembah through a Marxist feminist lens. While previous studies have examined women’s exploitation in literature and the industrial workforce, limited attention has been given to how literary texts depict women cigarette workers within the intersections of commodification, social reproduction, alienation, and identity fragmentation. This study adopts a qualitative descriptive approach employing critical textual analysis of the novel’s narrative structure, dialogues, and portrayals of women’s labor and bodily experience. The findings reveal that the novel positions female workers within unequal labor relations characterized by low wages, double workloads, workplace discipline, and restricted agency. Moreover, the logic of exploitation extends beyond the factory, encompassing the domestic sphere, where the home is portrayed as a site shaped by subsistence pressures and reproductive labor. From a Marxist feminist perspective, these conditions illuminate the interconnectedness of production, social reproduction, and women’s experiences of alienation. This study contributes to contemporary Indonesian literary scholarship by demonstrating how the novel articulates women’s exploitation not only as an economic issue but also as a process that influences domestic life and the construction of female subjectivity.